Factors affecting the intention to fully adopt the computer assisted audit tools and techniques (CAATTs) among external auditors in Jordan - Ayman Mohammad, Said Khasawneh (Universiti Malaysia Perlis (UniMAP), 2017)
Master of Science in Accounting